A Speech Act Analysis of Harvey Specter’s Conversation with The Male Characters in Suits - Kayne Hanson Laksmono (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
Speech acts are the most basic element of linguistic study to communicate effectively since it conveys the true intention of a word or a message to the listener. Speech acts are also crucial parts in communication since it becomes the connector between the speaker and the listener. Speech acts help us to understand and interpret the true meaning of every utterance. This research mainly focuses on locutionary and illocutionary.  Utterances spoken by Harvey Specter to Louis Litt and Mike Ross in a Netflix series called Suits were qualitatively analyzed using types of speech acts, namely assertive, commissive, declarative, expressive, directive (Searle, 1969). In Harvey’s utterances to both male characters, the three types of speech acts are found.